Medullary Sponge Kidney and Testicular Dysgenesis Syndrome: A Rare Association - Stefano Masciovecchio; Pietro Saldutto; Giuseppe Paradiso Galatioto; Carlo Vicentini (Case Reports in Urology)
The medullary sponge kidney is also known as Lenarduzzi’s kidney or Cacchi and Ricci’s disease from the first Italian authors who described its main features. A review of the scientific literature underlines particular rarity of the association of MSK with developmental abnormalities of the lower urinary tract and genital tract such as hypospadias and bilateral cryptorchidism. The work presented is the only one in the scientific literature that shows the association between the medullary sponge kidney and the testicular dysgenesis syndrome. A question still remains unanswered: are the MSK and TDS completely independent malformation syndromes occurring, in this case, simultaneously for a rare event or are they different phenotypic expressions of a common malformative mechanism? In the future we hope that these questions will be clarified.